On the significance of the effectiveness and productivity criteria of the new Criminal Procedure System - Choquehuanca, Nancy Carmen (2012)
The brand new Criminal Procedure Code, as a legal tool for an adversarial accusatory trait, aims to ensure that the operators of the criminal justice system behave with objectivity and professionalism, as part of the formula that characterizes it is to be agile, very swift, and mainly based on the principle of judicial economy, considering the cost-benefit for both the State and the system operator, this under indicators of efficiency, effectiveness and productivity; while who gives life to this body of law is the legal practitioner, the same one who should not necessarily be overly formalistic, but based on reasoning of transcendence and social reality, in order that users achive a real, serious and transparent legal certainty, i.e. social peace with justice; hence the observations that arise in this paper, aim to measure how effective or efficient both the actions and the decisions of the judges and prosecutors are in judicial work